Um modelo sociocognitivo para o autoperdão - Alencar, Thalita Lays Fernandes de (2021)
This thesis proposes a sociocognitive model about self-forgiveness, and an analysis of the relationship between the decentering ability and the types of self-forgiveness. The main objective of this study is to empirically test this typology, verifying: (1) the factorial organization of the justifications presented for self-forgiveness and (2) the relationship of these justifications with the decentering ability and age. To meet these objectives, the theoretical foundation for the proposed typology is first presented. Then, two empirical studies are described in two articles. The first article was a cross-cultural study with the aim of validating the Self-Forgiveness Reasoning Scale (ERA), an instrument built to represent the types of self forgiveness. Brazilian (n = 309) and Portuguese (n = 363) college students participated in the studies. The factorial validity of the scale was tested in two studies with samples from each country. Exploratory factor analyzes (study 1) indicated that the instrument has a bifactorial organization that explains about 60% of the total variance (α = 0.72 / 0.73). Confirmatory analyzes (study 2) corroborated a bifactorial organization with two types of self-forgiveness: egocentric and decentered. The results showed that the instrument has good psychometric properties and is suitable for assessing its intended purpose. In addition, significant correlations were found between types of self-forgiveness and two dimensions of empathy (empathic concern and perspective-taking), variables that represented an application of the decentering ability in an interpersonal domain. The second article sought to verify the differences by age in the type of self-forgiveness. A total of 151 students were organized in three age groups: G1 (7- 9 years), G2 (12-14 years) and G3 (17-19 years). The instruments used were: the ERA to assess the type of self-forgiveness and the Piaget's Mountain Task to assess the spatial perspective taking, a variable that represented an application of the decentering ability in an impersonal domain and, therefore, represented it in this study. The existence of correlation between these variables was corroborated, as proposed in the typology presented. The age-related effect also received empirical support as the more robust results of the analysis of variance followed theoretical assumptions and demonstrated a significant decrease in egocentric reasoning throughout development. Finally, in the final considerations, a general discussion of the results obtained in the two reported articles was presented, as well as reflections on future studies. It is considered that the studies presented met the established objectives and corroborated an organization of types of reasoning about self-forgiveness.